Ability in Intellectual Disability: The Culture of Inequality in Nigeria and Other Jurisdictions - Ukoh, Francis Nnamdi; Ukoh, Eberechi Catherine; Nwanzi, Joseph (Advances in Social Sciences Research Journal, 2023)
This paper examines the disputable issue of the culture of inequality in providing legal protection for children living with intellectual disabilities. It argues the disparity in the provision of educational and health services for persons living with intellectual disabilities by the Nigerian Government and identifies the gaps in the provisions of Sections 20 and 21 of the Nigerian Discrimination Act. These deficiencies obscure the ability of children living with disabilities (Down syndrome and Autism), which culminates in a domino effect from delayed intervention. It draws a comparative analysis from the United Kingdom and the United States of America as a standard for innovative legal frameworks in Nigeria. It concludes that non-governmental organisations must collaborate with the government to ameliorate Nigeria's poor education and health care, with a differential detour that rights to free education and health care for those with intellectual disabilities be justiciable for the Act's practicability.